Imunochromatographic strip test detection of anti-rK39 antibody for the diagnosis of Kala-Azar in an endemic zone of Bangladesh - Salam, Md. Abdus (Professional Medical Publications, 2008)
Objectives: A rapid immunochromatographic dipstick test (ICT) has become available for the qualitative detection of anti-Leishmania antibody using recombinant rK39 antigen. This study was carried out at the department of Microbiology of Rajshahi Medical College, Bangladesh, in order to evaluate the diagnostic potential of immunochromatographic dipstick test. Methodology: A total of one hundred cases including 60 admitted patients with strong clinical suspicion of kala-azar and 40 healthy controls were investigated for the performance of the ICT. Splenic smears were examined for microscopic detection of Leishman Donovan (LD) bodies obtained from the admitted patients only and smear-positive cases were considered as gold standard as well as confirmed cases of kala-azar. Results: Out of 60 suspected patients, fifty three (88.33%) were found smear-positive and fifty nine (98.33%) were positive for immunochromatographic strip test. All smear-positive cases were also positive for strip test. Voluntary healthy controls (40), which included twenty persons from the endemic zone and twenty from non-endemic zone of kala-azar, were found all negative for the strip test. The sensitivity and specificity of immunochromatographic strip test were found to be 100.00% and 86.95% respectively. Conclusion: Present study findings again reinforce that the immunochromatographic strip test is a simple, reliable and easy-to-perform non-invasive diagnostic tool for visceral leishmaniasis in the endemic area of Bangladesh.